A Note on LP-Sasakian Manifolds with Almost Quasi-Yamabe Solitons. (10th December 2021) - Yadav, Sunil Kumar; Suthar, D. L.; Shimelis, Biniyam
Abstract : We categorize almost quasi-Yamabe solitons on LP -Sasakian manifolds and their CR -submanifolds whose potential vector field is torse-forming, admitting a generalized symmetric metric connection of type α, β . Finally, a nontrivial example is provided to confirm some of our results.